RA08.05: ENDOSCOPIC THERAPY AND SURVEILLANCE VERSUS ESOPHAGECTOMY FOR EARLY ESOPHAGEAL ADENOCARCINOMA: A REVIEW OF EARLY OUTCOMES AND COST ANALYSIS. (14th September 2018) - Boshier, Piers; Wirsching, Andrea; Krishnamoorthi, Rajesh; Larsen, Michael; Irani, Shayan; Ross, Andrew; Low, Donald
Abstract: Background: Endoscopic therapy is considered to be comparable to esophagectomy with respect to oncologic outcomes in early (clinical stage T1) esophageal adenocarcinoma (EC). The current study aims to compare early outcomes and financial costs, associated with endoscopic versus surgical therapy for early EC. Methods: Retrospective review of patients undergoing either endoscopic or surgical therapy for cT1 EC between 2010 and 2015 at a single high-volume center. To ensure comparability between treatment groups only those patients who were deemed medically fit to undergo esophagectomy, regardless of ultimate management, were included. Cost analysis was performed for each patient group and was compared to procedural outcomes. Results: Forty-three patients met the inclusion criteria for this study (endoscopic therapy n = 20; esophagectomy n = 23). All patients who underwent endoscopic therapy had clinical stage T1A, whilst 15 patients in the esophagectomy group had T1B disease ( P < 0.001). Patient groups were well matched for all other baseline characteristics ( P > 0.05). For patients undergoing endoscopic therapy a median of six interventions were performed per patient (range 2–18). Same day discharge was achieved after 98% of all endoscopic procedures with 72% of cases performed under general anesthesia. Endoscopic dilations due to stricture formation were required in five (25%) patients after endoscopic therapy. Esophagectomy was associated with a median hospital stay of 9 (8–13) days and greater procedure specific morbidity compared to endoscopic therapy. Median treatment costs for patients undergoing esophagectomy were significantly greater than that incurred for patients receiving endoscopic therapy only (53, 849, 95%-confidence interval: 50, 541–88, 784 vs. 22, 640, 95%CI: 18, 754–46, 705, P < 0.001). The minimum cost associated with esophagectomy in the current study was approximately four times greater than for endoscopic therapy (40, 410 vs. 9236). In comparison the maximum cost incurred for surgical and endoscopic therapy were 247, 808 and 127, 508 respectively. Overall costs were significantly correlated to either number and severity or postoperative complications or number of endoscopic procedures performed ( P < 0.002). Conclusion: In patients with early EC endoscopic therapy was associated with lower rates of procedure specific morbidity compared to esophagectomy. Despite an increased number of interventions and longer duration of therapy, overall costs were significantly lower in patients undergoing endoscopic therapy when compared to esophagectomy. Disclosure: All authors have declared no conflicts of interest.